2008
DOI: 10.1007/s10895-008-0440-0
|View full text |Cite
|
Sign up to set email alerts
|

Er-Yb Codoped Ferroelectrics for Controlling Visible Upconversion Emissions

Abstract: Under a 980 nm laser pumping, quenching of green upconversion (UC) emission accompanied with enhancement of red UC emission observed was dominated by the energy back-transfer (EBT) process in Er(3+) and Yb(3+) co-doped PbTiO(3), BaTiO(3), and SrTiO(3) polycrystalline powders. The efficiency of the EBT process depends not only on Yb(3+) concentration but also on level match of the doped Er(3+) and Yb(3+) ions caused by the crystal fields with different symmetries. Our UC emission spectra and X-ray diffraction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…It is suggested that a cross-relaxation process is responsible for populating the 4 F 9/2 level and occurs via two resonant transitions: 4 F 7/2 → 4 F 9/2 and 4 I 11/2 ← 4 F 9/2 between neighboring Er 3+ ions [28]. The 4 F 9/2 → 4 I 15/2 transition produces the red emission around 640-680 nm [10]. In fact, cross-relaxation process is the main one populating the 4 F 9/2 level of Er 3+ in the higher concentration (2-3 mol%) of Er 3+ doped BTO nanocrystals, giving rise to the enhancement of the red emission, in agreement with the obtained experimental data (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that a cross-relaxation process is responsible for populating the 4 F 9/2 level and occurs via two resonant transitions: 4 F 7/2 → 4 F 9/2 and 4 I 11/2 ← 4 F 9/2 between neighboring Er 3+ ions [28]. The 4 F 9/2 → 4 I 15/2 transition produces the red emission around 640-680 nm [10]. In fact, cross-relaxation process is the main one populating the 4 F 9/2 level of Er 3+ in the higher concentration (2-3 mol%) of Er 3+ doped BTO nanocrystals, giving rise to the enhancement of the red emission, in agreement with the obtained experimental data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BaTiO 3 (BTO) is suitable for host matrix as UC phosphors because of its good properties, such as its low phonon energy (about 700 cm −1 ), good insulating property, and its chemical and physical stability. Up to now, some reports dealing with UC luminescence properties of BTO nanoparticles have been presented [10]. For instance, Patra et al prepared BTO: Er 3+ by sol-emulsion-gel method, and studied their UC fluorescence properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…The typical UC emission consists of two strong green bands and a weak red band located at 528, 548 and 656 nm originating from the intra 4f-4f electronic transitions 2 H 11/2 / 4 S 3/2 → 4 I 15/2 and 4 F 9/2 → 4 I 15/2 of the Er 3+ ions, respectively. Obvious level splits can be observed when the x value is more than 0.7, which can be attributed to the Stark splitting of the degenerate 4f levels under the strong crystal field [16]. The split is more remarkable with increasing x because of the larger asymmetric crystal field for the host material with larger tetragonality.…”
Section: Resultsmentioning
confidence: 98%
“…3. 21 The Er 3þ ion at 4 subsequently absorbs one photon and jumps to the 4 F 9/2 level, thus the enhanced population of the 4 F 9/2 state is of benefit of the red UC emission. It indicates that the emission colors can be easily tuned by adjusting the concentration of Yb 3þ ion.…”
Section: Resultsmentioning
confidence: 99%